Formulasi dan Evaluasi Mutu Fisik Sediaan Hand Cream Dari Ekstrak Kulit Pepaya (Carica papaya L.) - Andalia, Rizki (JURNAL ILMIAH FARMASI SIMPLISIA, 2024)
Papaya peel extract (Carica papaya L.) has antioxidant content that functions as a sunscreen and can moisturize the skin of the hands. However, it is rarely used in cosmetic preparations such as hand creams. This study aims to increase the utilization of papaya peel waste, determine that papaya peel extract can be formulated as a hand cream preparation, and determine the physical properties of the hand cream preparation produced. This research method is experimentally laboratory, formulating a hand cream with a variation in the concentration of papaya peel extract as an active substance, namely F1 (1%), F2 (1.5%), and F3 (2%). The evaluation of the physical quality of hand cream emulsion type test, organoleptic test, pH test, homogeneity test, dispersibility test, adhesion test, and viscosity test. The results showed that papaya peel extract with concentrations of 1%, 1.5%, and 2% could be formulated as a hand cream preparation. The results of the physical quality evaluation in the three formulations showed that the type of A/M emulsion (cream) is yellow in color, semi-solid, and has a distinctive smell of papaya peel. All homogeneous formulations have a pH value of 6.4 – 7, dispersion ability of 5.3 cm – 7 cm, adhesion ability ≥ 4 seconds, and a viscosity value of 1800 cPs – 5000 cPs. The results of the evaluation test of hand creams containing papaya peel extract of 1%, 1.5%, and 2% meet the physical quality requirements of hand cream preparations.